Enhancing Tourist Satisfaction And Revisit Intention Through Experience-Based Tourism At Rotterdam Fort - Suma Thesa; I Nyoman Sudiksa; I Gede Darmawijaya (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of tourist experience on satisfaction and revisit intention at Rotterdam Fort, Makassar, as well as to examine the mediating role of satisfaction. The research employed a quantitative approach by distributing questionnaires to 310 tourist respondents, and the data were analyzed using Partial Least Square (PLS). The results indicate that tourist experience has a positive and significant effect on both satisfaction and revisit intention. Furthermore, tourist satisfaction also has a significant influence on revisit intention and is proven to mediate the relationship between tourist experience and revisit intention. These findings support the Expectation Confirmation Theory, which emphasizes the importance of congruence between expectations and actual experiences in shaping satisfaction. Practically, the results of this study provide valuable insights for Rotterdam Fort’s management to enhance service quality, supporting facilities, and innovative attractions in order to create more satisfying experiences and foster tourist loyalty.